PENINGKATAN MOTIVASI DAN HASIL BELAJAR PADA BAHAN KAJIAN KONTRASEPSI MELALUI METODE LESSON STUDY YANG DILAKUKAN SECARA DARING - Erika Agung Mulyaningsih (CV Sintesia, 2023)
UNESCO said 73% of schools were closed for 3 months or more due to the Covid-19 pandemic. Face-to-face learning at Diploma III Midwifery Program has been stopped for more than 9 months. Efforts to achieve competence in Midwifery Education are a problem that must be solved innovatively. The purpose of this study was to improve student motivation and learning outcomes through the Lesson Study method. The method of this research is Classroom Action Research which is conducted in two cycles, each of which contains 3 x 100 minutes of face to face and 3 x 120 minutes of structured assignments. The research was conducted on third semester students on contraceptive study materials which consisted of 9 topics. The results of this study were obtained in the first cycle the lowest score was 30, the highest was 66, the class average score was 45. While in the second cycle, the lowest score was 38 and the highest score was 96, with a class average score of 68. Learning motivation 9 students (33.3 %) experienced an increase in motivation from the first cycle to the second cycle, while 37% of students still had high motivation but with an increased questionnaire score. Lesson study can increase student motivation and learning outcomes. Various innovations and creativity are needed for students and lecturers to continue learning and teaching in a pandemic situation which is supported by the management in improving the quality of learning